Age estimation accuracy based on Atlas London and Schour-Massler in Tionghoa ethnic children - Icha Artyas Annariswati; Shintya Rizki Ayu Agitha (Ikatan Radiologi Kedokteran Gigi Indonesia, 2021)
Objectives: Age estimation is an important factor in forensic science and needs to be known accurately because it can narrow the search when examining unidentified victims, determine the victim's age at death and is also useful in cases of adulteration of athletes, child guardianship, or to determine whether someone is of legal age. or not according to the law. This study aims to determine individual age estimates based on the London Atlas and Schour-Massler Atlas and compare the accuracy of the two methods. Materials and Methods: 70 panoramic radiographs consisting of 31 boys and 39 girls from Chinese ethnicity in Surabaya, aged 6-13 years (72-156 months). Samples were determined for dental age based on the London Atlas and the Schour-Massler Atlas. The data that has been obtained is then processed by statistical analysis with SPSS for Windows, with an inclusion level of p <0.05. Results: This study showed that the London Atlas was better and more accurate than the Schour-Massler Atlas with a lower mean error and there was no significant difference between the London Atlas dental age estimation and chronological age with p value = 0.426 in the left region and p = 0.429 in the right region (p>0.05). Conclusion: The results obtained from this study indicate that dental development based on the London Atlas and Schour-Massler Atlas can be used as a method to determine the estimated age of children from the range of 6 - 13 years in ethnic Chinese.